OPTIMALISASI DISKUSI KELAS MELALUI PEER ASSESSMENT DAN SELF ASSESSMENT UNTUK MENILAI KEMAMPUAN KOMUNIKASI LISAN MAHASISWA CALON GURU BIOLOGI - Juhanda, Aa (Universitas Tanjungpura, 2017)
This descriptive study aimed to obtain oral communication skills prospective biology teachers through peer and self assessment in class discussions. Subjects were 26 students of Biology Education Department 6th semester 2015/2016 academic year who contracted the courses of anatomy and physiology of the human body. The instrument used consisted of sheets of peer and self-assessment, as well as the student questionnaire. The result of research showed that the average of peer assessment for oral communication of students is different with the mean of self assessment. The spoken oral communication ability indicators that was revealed include: (1) choosing the most appropriate way to present the explanation of 66% (Good); (2) using tables, drawings, models to present an explanation of 62% (Good); (3) responds to a question from another student in the form of a convincing argument of 64% (Good); (4) interpret the obtained solution by 51% (Enough); (5) responds to a question from another student in the form of a convincing argument of 57% (Enough). Students responded positively to the implementation of peer and self assessment in lectures.Keywords : Peer Assessment, Self Assessment, Classroom Discussions, Oral Communication